Copro-Molecular Identification of Microsporidia in Rural Communities of Kapit Division, Sarawak - Rohiit, Baskaran; Anis Alisa, Bolhi; Clarissa Sudan, Jerry Langkop; Mohamad Ikh’wan Saputra, Mohamad Pajar; Siti Farah Norasyikeen, Sidi Omar; Khatijah, Yaman; Romano, Ngui (2025)
Introduction: Microsporidia are obligate intracellular parasites of growing global concern, particularly among immunocompromised populations. In Malaysia, the burden of microsporidiosis remains underexplored, especially within the general community, as most studies have focused on immunocompromised patients. Factors such as limited healthcare access, untreated water sources, and close human-animal interactions further increase the risk of transmission. In this context, the present study aims to determine the prevalence of microsporidia among the rural longhouse communities in Kapit, Sarawak.